2003
DOI: 10.1029/2002jd002106
|View full text |Cite
|
Sign up to set email alerts
|

TEM study of aerosol particles from clean and polluted marine boundary layers over the North Atlantic

Abstract: [1] Aerosol samples were collected from Punta del Hidalgo in the Canary Islands and Sagres in Portugal during June-July 1997 as part of the Aerosol Characterization Experiment-2 (ACE-2) over the North Atlantic Ocean. We studied individual aerosol particles using transmission and scanning electron microscopy. The major aerosol types include fresh and partly or completely reacted sea salt that consist of NaCl, mixed-cation (Na, Mg, K, and Ca) sulfate, Na 2 SO 4 , and NaNO 3 ; particles of industrial origin that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 54 publications
(76 reference statements)
14
91
1
Order By: Relevance
“…Because some particles in (ammonium)sulphates "mixed with carbon" and "without detectable carbon" subgroups might also contain unidentifiable soot particles (dark inclusions without clear morphological characteristics), the proportions for internally mixed soot/sulphate particles should be considered as minimum estimates. The strong internal mixing of soot is in line with other studies performed in clean background areas, far from soot emission sources (Pósfai et al, 1999;Hasegawa and Ohta, 2002;Li et al, 2003a;Okada et al, 2005). While freshly emitted soot is extremely hydrophobic, the aging processes such as coagulation, condensation and chemical reactions cause soot to become rapidly (in polluted conditions during less than a few hours; Johnson, 2005) more hydrophilic .…”
Section: Soot Particlessupporting
confidence: 69%
See 1 more Smart Citation
“…Because some particles in (ammonium)sulphates "mixed with carbon" and "without detectable carbon" subgroups might also contain unidentifiable soot particles (dark inclusions without clear morphological characteristics), the proportions for internally mixed soot/sulphate particles should be considered as minimum estimates. The strong internal mixing of soot is in line with other studies performed in clean background areas, far from soot emission sources (Pósfai et al, 1999;Hasegawa and Ohta, 2002;Li et al, 2003a;Okada et al, 2005). While freshly emitted soot is extremely hydrophobic, the aging processes such as coagulation, condensation and chemical reactions cause soot to become rapidly (in polluted conditions during less than a few hours; Johnson, 2005) more hydrophilic .…”
Section: Soot Particlessupporting
confidence: 69%
“…Images of sea salt particles with similar morphology and composition have been shown in several recent electron microscopy studies (e.g. Ebert et al, 2000;Li et al, 2003a). However, PM 1−3.3 sample 10 contained ordinary sea salt particles (36% of all analysed particles) and also other Narich particles without characteristic morphology and Mg-Ca-K ratios of sea salt (36% of all analysed particles; Table 4).…”
Section: Silicates and Metal Oxides/hydroxidesmentioning
confidence: 97%
“…The shape of deposited BC particles was caused by characteristics of BC because of similar shape and size of BC particles on the leaves or needles. The size and shapes of BC particles deposited on the polyethylene sheets in the present study were similar to those of BC particles that were previously detected by Li et al (2003) in the atmosphere by transmission electron microscopy (TEM).…”
Section: Bc Particles On the Polyethylene Sheetssupporting
confidence: 73%
“…Andreae et al (1986) unexpectedly found that a large fraction of mineral substances and sulfates in the marine boundary layer were internally mixed with sodium chlorides. Subsequently, several field studies have confirmed that a significant proportion of sea salts are internally mixed with sulfates and nitrates (Mouri et al, 1993;Laskin et al, 2002;Li et al, 2003a), while other research has revealed that the chloride components in sea salts acquire a coating of organic surfactants in polluted coastal environments or even at remote islands (Tervahattu et al, 2002a, b;Laskin et al, 2012;Chi et al, 2015). Electron microscopy and single-particle mass spectrometry have indicated that potassium chlorides in biomass burning smoke mix with soot and organics, and some even acquire an organic surface coating (Silva et al, 1999;Li et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%